Psychological and social impact of malocclusion in children and young adults - A review - Aasini Maria Georgina; Jasmine S Sundar; G Srinivas (Wolters Kluwer Medknow Publications, 2023)
Malocclusion is a major oral health problem, which is prevalent among all age groups. Malocclusion affects speech and mastication and causes pain. In psychosocial health, it may impact an individual's self-esteem due to self-perceived appearance and peer's opinions. This article aims to assess the effect of malocclusion on psychological and social health (i.e., quality of life, [QoL]) in children and young adults by reviewing the literature. Studies found to be relevant were identified in PubMed, Cochrane, and Google Scholar. Studies with data on malocclusion, factors influencing the treatment, and QoL associated with oral health in children and adolescents were considered for this review. After carefully scrutinizing the study objective, a total of ten full-text articles were selected and reviewed. Researcher's found that dental problems such as anterior tooth trauma or missing malocclusion affect the esthetics and psychological behavior of adolescents. Malocclusion can be socially and psychologically stigmatizing for young adults.